1981
DOI: 10.1103/physrevc.24.1778
|View full text |Cite
|
Sign up to set email alerts
|

ppelastic analyzing power from 318 to 800 MeV

Abstract: The maximum value of the analyzing power A for pp elastic scattering has been measured at 17' lab as a function of energy from 318 to 800 MeV. No unexpected energy dependent structure is observed at the 0.5%%uo level.NUCLEAR REACTIONS 'H(p, p}'H, E = 318 -800 MeV, measured A at Olab = 17 .The observation of energy dependent structure in proton-proton scattering has generated much interest recently. Significant structure has been observed in the medium energy range in measurements of Aoy, Aol, A~~~a nd ALL . ' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The beam-line polarimeters have been calibrated to 1% for a wellfocused beam spot [40]. Experience has shown that with a poorly focused beam the uncertainty increases to 2% as a result of increased contamination by quasifree scattering from carbon in the CH2 targets.…”
Section: Normalizationmentioning
confidence: 99%
“…The beam-line polarimeters have been calibrated to 1% for a wellfocused beam spot [40]. Experience has shown that with a poorly focused beam the uncertainty increases to 2% as a result of increased contamination by quasifree scattering from carbon in the CH2 targets.…”
Section: Normalizationmentioning
confidence: 99%
“…The uncertainties reported for the previous measurements and the overall systematic uncertainty of the target polarization measurement are the main contributors to the systematic uncertainty listed in each column. The systematic uncertainties in the beam ( -1% [19]) and scattered particle's ( -2'%%uo [20]) polarization measurements are not included (see text). were not used in these tests because of the low efficiencies of these chambers (a valid trajectory through each chamber system that supplied any histogram used in the tests discussed above was a prerequisite).…”
Section: Analysis Of the Scattering Datamentioning
confidence: 99%
“…The uncertainties in these previously measured quantities and the overall uncertainty in the target polarization ( -5% ) are included in the systematical uncertainties reported in Tables I-III. However, the systematical uncertainties in the beam polarization measurement [19] ( -1%) and the scattered particle's polarization measurement [20] (-2%) are not included in the values given in Tables I -III. These should be added to the total uncertainty.…”
Section: Analysis Of the Scattering Datamentioning
confidence: 99%
See 2 more Smart Citations